Perencanaan Jalan Alternatif di Desa Tiyingtali – Tumingal, Kabupaten Karangasem, Provinsi Bali - Diva, I Wayan Ditya Maha; Asmani K., Anak Agung Rai; Aryastana, Putu (Universitas Ibn Khaldun, 2024)
Road is an access that connects one place to another in one land. This alternative road planning aims to reduce travel time from existing roads. This research was carried out in several steps, namely: problem formulation, location survey, data collection, data processing so that relevant analysis is obtained. The research location will be planned on the Tiyingtali - Tumingal road section, Abang District, Karangasem Regency. The results of this study produce technical calculations for Horizontal Alignment with several types of bends produced, namely: 1 (one) unit of Spiral Circle Spiral bend, and 2 (two) units of Spiral Spiral Bend. With thick pavement, namely Surface Course 2.5 cm, Base Course 10 cm and Sub Base Course 10 cm. So that road users can pass safely and comfortably.